Evaluation of a Brazilian School Violence Prevention Program (Violência Nota Zero) - Stelko-Pereira, Ana Carina (Pensamiento psicológico, 2015)
Objective. This study assessed the implementation of a program to decrease the levels of school violence,maximize student engagement, and improve teachers’ well-being. Method. In total, 71 students (21 from theintervention school and 50 from the control group school); 13 educators (8 from the intervention school and 7from the control group school) answered the study instruments. Both public schools were located in a highlyvulnerable area in Brazil. The following measures prior and post intervention were collected: School ViolenceScale; School Engagement Scale (students) and Goldberg’s General Health Questionnaire; School ViolenceScale (teachers). Follow-up measures were taken with the intervention school after eight months. The Programconsisted of twelve 90-minute sessions to educators on school violence prevention, involving presentations,discussions and classroom exercises. Results. Significant reductions in self-reported perpetration of violenceby students (M pre-intervention = 15, M post-intervention = 13, z = -2.5, p = 0.01), and of teachers’ mentalhealth problems (Mdn pre-intervention = 1.8, Mdn post-intervention = 1.4, z = 2.1, p = 0.03) were noticedin the experimental group after the intervention, in comparison to the control school. However, the programdid not improve school engagement, nor did it diminish student victimization by staff or teacher victimizationby students. Lower levels of peer-to-peer violence, as reported by students were maintained in the follow-upassessments. Conclusion. Despite the limitations of the study, such as a small sample, the existence of pertinent(although limited) results is encouraging, as there are not many similar initiatives in developing countries